Antidiabetic effect of Nigella sativa compared with metformin on blood glucose levels in streptozotocin induced diabetic albino wistar rats - Sadiq, Neeraj; Subhani, Ghulam; Fatima, Syeda Ayesha; Nadeem, M.; Zafer, Shaima; Mohsin, M. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Antidiabetic drugs are many but all of them have adverse effects ranging from simple side effects to serious side effects like hypoglycemic coma. We need alternative drugs which will not only lower blood sugar level but have fewer side effects. One such daily use ingredient in our food is Nigella sativa (kalonji) which has many properties. Methods: This was an objective study in an experimental animal. We divided albino wistar rats into six groups each group with six rats. Diabetes was induced using drug streptozotocin. Three doses of Nigella sativa 0.5 ml, 1 ml, 1.5 ml orally per rat were used. Metformin (100 mg/kg body weight) was used as standard drug. Blood sugar was estimated using glucometer on day 0 (starting day of treatment), day 5, day 10, day 20, day 40. The effect of Nigella sativa was compared with metformin group using the Anova test. Statistical analysis was done using SPSS software version 20. Results: Nigella sativa (NS) produced significant hypoglycemic effect. NS in the dose of 0.5 ml, 1 ml and 1.5 ml produced significant reduction in blood glucose in comparison to day 0. Metformin also (100 mg/kg body weight) produced significant reduction in blood glucose on day 20 and day 40. Comparison of hypoglycemic effect of Nigella sativa is not significantly different on day 10 (1 ml) and day 20 (1.5 ml) in comparison to Metformin (100 mg/kg body weight). Histopathological examination showed that there was partial regeneration of beta islet cells of pancreas by 1.5 ml of Nigella sativa which were damaged due to streptozotocin treatment. Conclusions: Alternative method of treatment for diabetes is very much needed and the study shows the use of the spice (Nigella sativa) daily can lower the blood sugar levels and can serve as an alternative treatment of diabetes mellitus.